Leveraging and Improving Refill Protocols at Your Health System - Tokazewski, Jeffrey T.; Peifer, Maryanne; Howell, John T., III (Applied Clinical Informatics, 2022)
Objectives Medication refill processing is a repetitive and predictable time-intensive task for ambulatory primary and specialty care. Refill protocols are a clinical decision support (CDS) tool that allows clinicians to quickly and safely determine appropriateness of a refill request. Our health system opted to improve the quality and breadth of electronic health record vendor-supplied protocols to consistently leverage best practices and emerging evidence and to create novel protocols that further support clinicians.Methods We established a refill protocol governance group to guide new protocol build and to review existing protocols regularly to keep current with emerging guidelines. Data-driven prioritization was used to create new protocols for the most frequently refilled medications, as well as for less-prescribed but higher risk medications. Ad-hoc specialist inclusion as subject-matter experts provided greater detail, accuracy, and broader consensus in protocol criteria.Results Approximately 11 million refills are processed each year by our health system's providers. The proportion of refill requests supported by a protocol increased over a 2-year period from 49 to 82%, representing a net increase of 3.63 million refills in the second measurement year as compared to the start of the first measurement year. All published refill protocols were reviewed by the governance group over the measurement years for compliance with clinical guidelines. In addition to the structure of the refill protocols' CDS, the process was supported by filters that enable practices to quickly approve refills that pass protocol, providing more time for clinicians to review refills that fail a protocol or for which no protocol exists.Conclusion A refill protocol is a valuable CDS tool that can improve efficiency, effectiveness, and user satisfaction when processing refill requests. A refill protocol governance structure is an effective way to review, edit, and build refill protocols within a health system.
Keywords: primary care; prescription; electronic health record; protocols; clinical decision support